Understanding challenges of parental involvement from the perspective of the parents of visually impaired learners in Pakistan - Malik, Shazia; Abdul Manaf, Umi Kalthom; Ahmad, Nor Aniza; Ismail, Maimunah (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
Parental involvement, as one of the most widely researched and discussed issues. It has been characterized by a variety of meanings, definitions and frameworks. Such notions and definitions provide a foundation for solving parental involvement challenges in the education of the visually impaired learners. This research discusses the parental involvement challenges from the perspectives of the parents of visually impaired learners by using a qualitative approach with semi-structured interviews of selected parent participants from two public secondary level institutes of the visually impaired learners Lahore, Pakistan. This paper endeavors to answer the questions like: What are the parental involvement challenges as faced by parents of visually impaired learners? What are the ways to cope with parental challenges? The findings of the paper indicate that deepen understanding of parental challenges that inhibit parental involvement of the parents of visually impaired learners in their education. There are five basic challenges emerged from data as the main themes, which are being parents of visually impaired learners, No acceptance in society, less parental involvement, parental grief, and parental intentions. These parental challenges show that parents of visually impaired learners are facing very difficulty in handling their disabled children and they need to cope with parental challenges with the teachers’ efforts collaboratively. Finally, the suggestions are put forward to cope with parental challenges towards their involvement in the education of their visually impaired learners.